DropQuest: Game-Based Learning for Chemistry - Terawat Kanjanapanwong; Techin Kowprasert; Sirion Vittayakorn (2022 19th International Conference on Electrical Engineering/Electronics, Computer, Telecommunications and Information Technology (ECTI-CON), 2022)
Although Chemistry is one of the fundamental subjects in high school that is strongly integrated in our daily life, it is one in which most students perform poorly in the university admission exam. One of the main reasons is an inappropriate learning approach. The traditional learning approach which is widely used in schools has several limitations. Thus, a game-based learning approach has been explored to increase students’ participation and interest. In this work, we aim to develop a multi-player chemistry game for Android phones that encourages student learning performance called DropQuest for Chemistry: Game-Based Learning for Chemistry. In our game, players must answer a series of questions organized in categories in a limited time to review and test their knowledge about the Atomic and Periodic Table. The experimental results demonstrate that participants love to play DropQuest with friends and they think the game provides both enjoyment and knowledge about elements of the periodic table. The experimental results demonstrate that our game enhances the players’ knowledge by 7% and achieves the average satisfaction score of 4.13 ± 0.33 out of 5 which outperforms both an interactive web-based periodic table and a game-based learning application by 6.0% and 9.9%.
Keywords: Educational Games and Gamification; Mobile Learning in Education; Teaching and Learning Programming